Empowerment as a Mediation of Organizational Support - Suhermin Suhermin (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The hospital is one of the health facilities which has a function to carry out primary health efforts or referral health and supporting health efforts. One of the elements implementing service activities and the spearhead of a hospital's health services is the nurse. The quality of the nurses determines the performance of the hospital. This study aimed to test and analyze perceived organizational support on psychological empowerment, structural empowerment, and organizational commitment. This research was conducted on 72 nurses of Muhammadiyah Tuban Hospital. The sampling technique used saturated sampling; all population members were used as samples. The type of data used is primary data using a questionnaire. Data analysis techniques using PLS. The results showed that perceived organizational support can increase psychological and structural empowerment but cannot increase organizational commitment. Well-implemented psychological empowerment and structural empowerment can increase organizational commitment.